Prevalence and Genotyping of Microsporidian Parasites in Dogs in Turkey: Zoonotic Concerns. (24th March 2019) - Duzlu, Onder; Yildirim, Alparslan; Onder, Zuhal; Ciloglu, Arif; Yetismis, Gamze; Inci, Abdullah
Abstract: Microsporidia are opportunistic pathogens that infect a wide range of invertebrates and vertebrates. To assess the potential role of dogs in the transmission of these zoonotic pathogens, a total of 282 fecal samples from dogs in the Central Anatolia Region of Turkey were analyzed by utilizing species specific polymerase chain reaction for the four most frequent human microsporidia. Two microsporidia species were recognized in 41 samples (14.5%). Encephalitozoon intestinalis was detected in 35 samples (12.4%) and it was the most common microsporidium. The second microsporidium, E. cuniculi, was identified in six (2.1%) of the samples. Sequence analysis of the intergenic spacer of the ribosomal ribonucleic acid (RNA) internal transcribed spacer (ITS) gene revealed the presence of three E. intestinalis haplotypes closely associated with each other. No polymorphic region was found among the ITS sequences of E. cuniculi isolates and they were characterized as genotype III. This study provides the first data on the zoonotic microsporidia species from dogs in Turkey.